2015
DOI: 10.1145/2796314.2745848
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Study of Flash Memory Failures in the Field

Abstract: Servers use flash memory based solid state drives (SSDs) as a high-performance alternative to hard disk drives to store persistent data. Unfortunately, recent increases in flash density have also brought about decreases in chip-level reliability. In a data center environment, flash-based SSD failures can lead to downtime and, in the worst case, data loss. As a result, it is important to understand flash memory reliability characteristics over flash lifetime in a realistic production data center environment run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(149 citation statements)
references
References 27 publications
5
144
0
Order By: Relevance
“…In the following, however, we will go beyond the manufacturer specifications and look at the basic physical mechanisms at the heart of the reliability issues. Since this is an extremely large field, we restrict our discussion to issues that develop with memory usage, neglecting for example defect-related issues, time-zero problems such as V T placement, cell-to-cell interference and many others, for which we refer the reader to other overviews of Flash memory reliability that are available in the literature, leaning either toward a device/technology [27,[51][52][53][54][55][56][57][58][59] or user [60][61][62] viewpoint.…”
Section: Nand Flash Memory Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, however, we will go beyond the manufacturer specifications and look at the basic physical mechanisms at the heart of the reliability issues. Since this is an extremely large field, we restrict our discussion to issues that develop with memory usage, neglecting for example defect-related issues, time-zero problems such as V T placement, cell-to-cell interference and many others, for which we refer the reader to other overviews of Flash memory reliability that are available in the literature, leaning either toward a device/technology [27,[51][52][53][54][55][56][57][58][59] or user [60][61][62] viewpoint.…”
Section: Nand Flash Memory Reliabilitymentioning
confidence: 99%
“…It has also been found [262] that repeated RD on partially-programmed blocks leads to an increased BER when the remaining pages are programmed, suggesting that extensive RD can lead to a degradation of the program characteristic of the cell. In any case, it has been claimed [61] that RD errors are not the prevalent ones in SSDs used in servers. …”
Section: Read Disturbmentioning
confidence: 99%
“…SSD prices are dropping and they continue to replace disk storage [118], and high-speed persistent memory is expected to become practical soon. Interconnects between processors are also expected to increase in speed.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…A recent Facebook study [40] showed that SSDs using flash memory do not degrade monotonically as flash wears but go through several distinct periods, depending on when failures emerge and are detected, and the effect of read disturbance is not the predominant source of errors in SSDs. This study was done on the use of SSDs for hot data, which lends support to our claim that extending service life of SSDs should be cost efficient in an archival setting.…”
Section: System Failure Modelingmentioning
confidence: 99%